Brain tissue saving effects by single-dose intralesional administration of Neuroprotectin D1 on experimental focal penetrating brain injury in rats. (June 2019) - Berg, Rand Wilcox Vanden; Davidsson, Johan; Lidin, Erik; Angéria, Maria; Risling, Mårten; Günther, Mattias
Highlights: Traumatic brain injury causes an inflammatory response in the brain. No medication has so far proven effective to lower the inflammation. NPD1 reduced brain lesion size in rats after experimental traumatic brain injury. NPD1 was administered directly into the lesion instead of systemically. Future studies should aim at exact mechanisms of tissue sparing of NPD1. Abstract: Traumatic brain injury (TBI) is followed by a secondary inflammation in the brain. Neuroprotectin D1 (NPD1) is synthesized from docosahexaenoic acid (DHA) and has anti-inflammatory and antiapoptotic effects in experimental models of neurodegenerative disease and brain ischemia-reperfusion. It is not known whether intralesional administration of NPD1 ameliorates inflammation and cell death after severe TBI. We therefore investigated the effects of NPD1 following a severe form of focal penetrating TBI. A total of 30 male Sprague-Dawley rats weighing between 350 and 450 g were exposed to focal penetrating TBI or sham surgery. The rats were randomized to NPD1 treatment (50 ng intralesionally, immediately following TBI) or no treatment. The rats were sacrificed at 24 or 72 h. All subgroups consisted of 5 rats. Brains were removed, fresh frozen, cut in 14-µm coronal sections and subjected to Fluoro-Jade, TUNEL, MnSOD, 3-NT, COX-2, Ox-42 and NF-κB immuno-staining and lesion size analyses. NPD1 decreased the lesion area at 72 h compared to no treatment with a mean change 42% (NPD1 14.1 mm 2 ; no treatment 24.5 mm 2 ) (p < 0.01). No difference was detected in markers for neuronal degeneration, apoptosis, anti-inflammatory or antioxidative enzymes, or immune cells. In conclusion, single-dose intralesional administration of NPD1 had brain tissue sparing effects after focal penetrating TBI, which may be beneficial in preventing brain tissue damage, making NPD1 a potential candidate for further clinical applications. Exact mechanisms of action could not be determined and it is possible that continuous or multiple administration regimens may increase efficacy in sequential preclinical studies.